2014
DOI: 10.2174/0929867320666131119154018
|View full text |Cite
|
Sign up to set email alerts
|

Receptors of Peptides as Therapeutic Targets in Epilepsy Research

Abstract: Neuropeptides are signaling molecules participating in the modulation of synaptic transmission. Neuropeptides are stored in dense core synaptic vesicles, the release of which requires profound excitation. Only in the extracellular space, neuropeptides act on G-protein coupled receptors to exert a relatively slow action both pre-and postsynaptically. Consequently, neuropeptide modulators are ideal candidates to influence epileptic tissue overexcited during seizures. Indeed, a number of neuropeptides have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 320 publications
(381 reference statements)
3
34
0
Order By: Relevance
“…Neuropeptide modulators are ideal candidates to influence epileptic tissue overexcited during seizures, because they have longer halflives allowing modulation of neuronal and network activity over prolonged periods, potentially setting the seizure threshold. Neuropeptides, stored in LDCVs, 146 are released upon high frequency stimulation that occurs during seizures (Kovac and Walker, 2013;Dobolyi et al, 2014; see section I). Indeed, galanin and a number of other neuropeptides are implicated in epilepsy pathology and many are considered to participate in endogenous neuroprotective actions via receptors in the hippocampus, a focus of seizures in temporal lobe epilepsy (Lerner et al, 2010;Kovac and Walker, 2013).…”
Section: E Physiologic and Pharmacologic Actions Of Galanin In The Dmentioning
confidence: 99%
“…Neuropeptide modulators are ideal candidates to influence epileptic tissue overexcited during seizures, because they have longer halflives allowing modulation of neuronal and network activity over prolonged periods, potentially setting the seizure threshold. Neuropeptides, stored in LDCVs, 146 are released upon high frequency stimulation that occurs during seizures (Kovac and Walker, 2013;Dobolyi et al, 2014; see section I). Indeed, galanin and a number of other neuropeptides are implicated in epilepsy pathology and many are considered to participate in endogenous neuroprotective actions via receptors in the hippocampus, a focus of seizures in temporal lobe epilepsy (Lerner et al, 2010;Kovac and Walker, 2013).…”
Section: E Physiologic and Pharmacologic Actions Of Galanin In The Dmentioning
confidence: 99%
“…Previous work demonstrated that dynorphin was upregulated in the HIPP following inhibition of NMDA receptors, in a pCREB-dependent manner (Rittase et al 2014), and others have shown that dynorphin inhibition of NMDA receptors appears to be pH dependent (Kanemitsu et al 2003). Interestingly, KORs and dynorphin in the HIPP have also been heavily investigated for their potential role in epilepsy (Clynen et al 2014, Dobolyi et al 2014). Dynorphin levels are elevated in the HIPP following a kainic acid induced seizure in rats (Rocha & Maidment 2003).…”
Section: Circuitrymentioning
confidence: 99%
“…Several peripheral peptides produced in the gut and associated tissues have been suggested to link changes in body metabolism with central nervous system functions and, thus, may be critical regulators in various pathophysiological conditions, including control of neuronal excitability in epilepsy (83–86). Peptide hormones are short molecules composed of approximately 3–100 amino acid residues, characterized by a structure simpler that than for proteins.…”
Section: New Hypothesis: Peptide Hormones As Possible Mediators Of Kdmentioning
confidence: 99%
“…In contrast to this variety of appetite-suppressing hormones, ghrelin is the only peripheral peptide with orexigenic properties and is mainly produced in the stomach (117, 118). Interestingly, some of the hormones displaying food intake regulatory properties also possess antiseizure effects (86, 119) (Table 3). …”
Section: New Hypothesis: Peptide Hormones As Possible Mediators Of Kdmentioning
confidence: 99%